PENGARUH KINERJA KARYAWAN DAN PENGAWASAN TERHADAP DISIPLIN KERJA PERUSAHAAN - Imam Muhayat (Jurnal Bisnis Darmajaya, 2015)
Human resources should not only be viewed as an object , but also a subject in the process of achieving organizational goals / agencies . The condition is a challenge to increase the role of human resources in particular employees of PT . Miki Oleo , to be able to utilize a variety of conditions and overcome challenges or obstacles in the atmosphere of a rapidly changing nation . Supervision is the execution of tasks can be executed according to plan and the legislation in force . It is hoped that the weaknesses and deficiencies in the work can be optimally repaired , so that in the future can be achieved better employment outcomes . Without intensive supervision feared many employees that work are not responsible . Supervised have prevented the emergence of cheating and misappropriation and leakage due to abuse of authority that will ultimately harm . There are variants or other factors that affect the relationship between supervision and discipline of work either individually or jointly with job performance . There is a positive relationship between supervision and discipline of working with job performance either individually or jointly , or in other words in PT . Miki Oleo , Ha relationship between supervision and discipline of working with job performance either individually or jointly received and tested . The relationship between supervision and discipline of working with performance of work under the supervision of labor discipline is strong enough and the relationship between the discipline of working with performance of work under the supervision of the surveillance isstrong.Keywords : Employee Performance , Monitoring and Discipline Work Company